2010
DOI: 10.1002/etc.152
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific distribution and whole‐body burden estimates of persistent organic pollutants in the bottlenose dolphin (Tursiops truncatus)

Abstract: Most exposure assessments for free-ranging cetaceans focus on contaminant concentrations measured in blubber, and few data are available for other tissues or the factors governing contaminant distribution among tissues. The goal of this study was to provide a detailed description of the distribution of persistent organic pollutants (POPs) within the common bottlenose dolphin (Tursiops truncatus) body and assess the role of lipid dynamics in mediating contaminant distribution. Thirteen tissues (brain, blubber, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…4D), like mice and chickens. Our observations suggest that low brominated congeners might have a higher capacity to penetrate the BBB and accumulate in the brain, whereas high brominated congeners such as BDE-209 might have less potency to go through the barrier, perhaps as a result of the high molecular weight and size of high brominated congeners (Li et al, 2014;Yordy et al, 2010). In another words, the BBB might hinder high brominated congeners such as BDE-209 more effectively than low brominated congeners, which is consistent with previous studies Yang et al, 2011).…”
Section: Brain/liver Ratios Of Pbde Concentrationssupporting
confidence: 90%
See 1 more Smart Citation
“…4D), like mice and chickens. Our observations suggest that low brominated congeners might have a higher capacity to penetrate the BBB and accumulate in the brain, whereas high brominated congeners such as BDE-209 might have less potency to go through the barrier, perhaps as a result of the high molecular weight and size of high brominated congeners (Li et al, 2014;Yordy et al, 2010). In another words, the BBB might hinder high brominated congeners such as BDE-209 more effectively than low brominated congeners, which is consistent with previous studies Yang et al, 2011).…”
Section: Brain/liver Ratios Of Pbde Concentrationssupporting
confidence: 90%
“…Besides differences in BBB function among vertebrates, patterns of PBDEs accumulation in the brain could result from other factors, such as differences in lipid compositions of the brain relative to the liver and lipid mobilization (Barni et al, 2014;Jorgensen et al, 1997;Yang et al, 2011;Yordy et al, 2010). Previous studies in vitro have shown that the affinity of PCBs for neutral lipids (triglycerides) is higher than for polar Fig.…”
Section: Brain/liver Ratios Of Pbde Concentrationsmentioning
confidence: 99%
“…Adult female cetaceans transfer the majority of their body burden of lipophilic contaminants (approximately 80%) to their calves through lactation (Cockcroft et al, 1989;Yordy et al, 2010b). In contrast, male cetaceans have no substantive mechanism for offloading contaminants, thus body burdens increase over their lifespan (Wells et al, 2005;Yordy et al, 2010b).…”
Section: Remote Biopsy Sample Analysismentioning
confidence: 97%
“…Several studies have found that POPs and T-Hg (total mercury) concentrations in the tissues of dolphins are highly variable in space and time (Balmer et al, 2015;Bryan et al, 2007;Fair et al, 2007;García-Alvarez et al, 2014;Kucklick et al, 2011;Miller et al, 2011;Stavros et al, 2008;Stavros et al, 2007;Woshner et al, 2008;Yordy et al, 2010). For example, the sum of the 6 NDL-PCBs (Non Dioxin LikeePolyChlorinatedBiphenyls) concentration is 5 times higher in male bottlenose dolphins living in the metropolitan area of the Biscayne Bay (near Miami) than those living off the rural coast a few miles south (Litz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%